Flavonoid content analysis of Brebes red 0nion skin waste flour as a low-cholesterol duck fodder mixture - Yan El Rizal Unzilatirrizqi; Syahidah Mutmainah; Akh Khotib Kurniawan (International Journal of Basic and Applied Science, 2022)
Brebes is one of the district regency in Central Java province which is famous for the production of red onions and salted eggs. This affects the percentage of onion waste produced and the need for duck fodder which is always increasing in price. The aim of this research is to make flour from raw material of red onion skin as a mixture of duck fodder. The research was done experimentally by testing the flavonoid content in red onion skin, making red onion skin flour, and testing the flavonoid content of red onion skin flour. The results showed that the flavonoid content of red onion skin was 3.54% and the flavonoid content of red onion skin flour was 4.35%. So, it can be concluded that red onion skin flour is suitable for mixed with duck fodder to get low-cholesterol duck.